2012
DOI: 10.1118/1.3673068
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cone beam CT angiography of carotid and cerebral arteries using canine model

Abstract: Purpose: This research is designed to develop and evaluate a flat-panel detector-based dynamic cone beam CT system for dynamic angiography imaging, which is able to provide both dynamic functional information and dynamic anatomic information from one multirevolution cone beam CT scan. Methods: A dynamic cone beam CT scan acquired projections over four revolutions within a time window of 40 s after contrast agent injection through a femoral vein to cover the entire wash-in and wash-out phases. A dynamic cone be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Review of the literature found no high-resolution CT or CTA studies of the dog’s normal cranial circulation. An experimental study was published using a dynamic cone beam CT scan of the entire wash-in and wash out phases of a femoral vein injection in a dog [ 12 ]. The resulting images showed the major external carotid arterial branches.…”
Section: Introductionmentioning
confidence: 99%
“…Review of the literature found no high-resolution CT or CTA studies of the dog’s normal cranial circulation. An experimental study was published using a dynamic cone beam CT scan of the entire wash-in and wash out phases of a femoral vein injection in a dog [ 12 ]. The resulting images showed the major external carotid arterial branches.…”
Section: Introductionmentioning
confidence: 99%